2014
DOI: 10.1039/c4ob01486c
|View full text |Cite
|
Sign up to set email alerts
|

Imides modified benzopicenes: synthesis, solid structure and optoelectronic properties

Abstract: Imide-modified polycyclic aromatic hydrocarbons can be widely applied in the field of optoelectronic materials. In this work, we have synthesized four novel functionalized benzopicenes and characterized their solid structures and optoelectronic properties. The fluorescence of the four functionalized benzopicenes showed red shifts with increasing solvent polarity; the quantum yields are high in the solution state and moderate in the solid state. The single crystal structures show that the benzopicenes adopt a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 117 publications
(18 reference statements)
0
12
0
Order By: Relevance
“…[3] Recently, we used 1,8-naphthalimide I as a building block to construct a series of benzopicenediimides III (Scheme 1). [4] Trinaphthylene carboximide 2, which can be regarded as the trimer of 2,3-naphthalimide 1, was reported by Wu and co-workers, and its relative low LUMO level made it a promising n-type semiconductor candidate. [5] Triptycene was first reported by Bartlett and co-workers in 1942, but its synthesis suffered from lengthy procedures and harsh conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Recently, we used 1,8-naphthalimide I as a building block to construct a series of benzopicenediimides III (Scheme 1). [4] Trinaphthylene carboximide 2, which can be regarded as the trimer of 2,3-naphthalimide 1, was reported by Wu and co-workers, and its relative low LUMO level made it a promising n-type semiconductor candidate. [5] Triptycene was first reported by Bartlett and co-workers in 1942, but its synthesis suffered from lengthy procedures and harsh conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[22] The key intermediate 4 was synthesized in 70 %y ield by means of ap alladium-catalyzed cross-coupling reaction. [11] Subsequently,atwofold palladium-catalyzed Buchwald amination reactionwas performed to give 1a-d in 75-88% yield. [23] The chemical structures of the new compounds were determinedb ys tandard spectroscopic characterizations, such as NMR spectroscopy and mass spectrometry (see the Supporting Information).…”
Section: Synthesismentioning
confidence: 99%
“…Our previous work indicated that the alkyl chain length and the introductiono ft he methoxy group had virtually no influence on the packing motif of these benzopicenediimides. [11] On the contrary,t he introduction of different functional groups onto the carbazole nitrogen has ac leari nfluence on the packing motif of dibenzocarbazolediimides. Compound 1a was packed in ah erringbone motif with al arge herringbone angle of 142.18,a sp romoted by p···p stacking interactions and weakC À H···p and CÀH···O hydrogen bonds, whereas 1d showed ao ne-dimensional lamellar packing motif that might be favorable for intermolecular charge transport (Figures S4 andS 5i nt he Supporting Information).…”
Section: Crystal Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…11 The syntheses of compounds 4a and 5a have been reported in our previous work. 12 In order to improve the solubility, longer alkyl chains Scheme 2. Synthesis of Compounds 1a,b and 2a,b were introduced and the synthetic procedures used to prepare 4b and 5b were similar to that described for compounds 4a and 5a.…”
mentioning
confidence: 99%